The evolution of viceroyal public spaces regarding Ricardo Palma’s tradition «La casa de Pizarro» («Pizarro’s house») - Taboada Briones, Sebastian Jesús (2023)
This article analyzes «La casa de Pizarro», a text included in the Tradiciones peruanas, a work of the writer, journalist and politician Ricardo Palma. It seeks to elucidate the influence of public spaces and how they reflect the state of Peruvian daily life in the 16th century, focusing on the place where Francisco Pizarro lived, before the construction of the Peruvian Government Palace. On the other hand, it is explained how the changes occurred in this place influence and how this neighborhood, economically valued low, becomes one of the main points of commerce in downtown Lima. Finally, the historical importance of this building is presented, as well as its cultural value today, and the challenge of the authorities to recover public spaces in a city as chaotic as Lima.